PEDOMAN FIQH LINGKUNGAN HIDUP DALAM PERSPEKTIF PENEGAKAN HUKUM LINGKUNGAN MELALUI PENERAPAN INSTRUMEN HUKUM ADMINISTRASI - Ali Faisal1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2013)
Fiqh of the environment is a set of rules of conduct ecological Muslim communities established by the competent based on the text with the aim of achieving Syar'iah goodnes together and preserve the environment, the Qur'an gave spiritual information to people to be friendly to the earth, because the earth is a survival of humans and other living things, so in this case the law enforcement administration officials should be able to understand and apply these guidelines as a basis forenvironmental jurisprudence in law enforcement with the use of the instruments of administrative law, article writing is done by using a normative-descriptive-analytical, and aimed to determine the guidelines for environmental jurisprudence in the perspective of law enforcement models using instruments of administrative law